A review of the genus Dolgoma Moore from India, with notes on the genus taxonomy and descriptions of a new genus, four new species and a new subspecies (Lepidoptera, Erebidae, Arctiinae, Lithosiini) - Singh, Navneet; Kirti, Jagbir Singh; Datta, Harvinder Singh; Joshi, Rahul; Volynkin, Anton V. (Zootaxa, 2019)
In the present paper, we review the genus Dolgoma from India, establish three species-groups and describe a new species, D. xanthoma N. Singh, Kirti, Datta & Volynkin, sp. nov. and a new subspecies, D. rectoides arunachala N. Singh & Joshi, ssp. nov. A new genus, Teuloma Volynkin & N. Singh, gen. nov. is established for Lithosia oblitterans Felder like species. Eight species are included here under Teuloma gen. nov., with five species known from India. Three of them are new for science and described below: T. microoblitterans N. Singh, Kirti & Datta, sp. nov., T. neooblitterans N. Singh, Joshi & Kirti, sp. nov. and T. falsinebulosa N. Singh, Kirti, Datta & Volynkin, sp. nov. Eight new combinations are established: Dolgoma steineri (Holloway, 2001), comb. nov., D. locus Bucsek, 2012, comb. nov., Teuloma oblitterans (Felder, 1868), comb. nov., T. montanebula (Holloway, 2001), comb. nov., T. nebulosa (Walker, 1862), comb. nov., T. divisa (Walker, 1862), comb. nov., T. setiniformis (Hampson, 1900), comb. nov. and Wittia lucida (Fang, 2000), comb. nov. In addition, checklists of presently known species of Dolgoma and Teuloma gen. nov. are provided.